"Economic history of India, 1857 - 1947" - "Roy, Tirthankar" (New Delhi, 2000)
This comprehensive and updated textbook on the economic history of colonial India presents a lucid account of the factors that shaped economic change in colonial India in the late-nineteenth and early-twentieth centuries.
Keywords: Economic history - India - 1857 - 1947